Analysis of the Extent of Red Light Running in Minna, North-Central Nigeria - SAMUEL MEDAYESE; MOHAMMED TAUHEED ALFA; NELSON T.A ABD’RAZACK; FAITH O. AGBAWN (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
This research pursued the objectives of assessing the awareness, perception, and levels of adherence of road users to traffic rules and regulations. The study was carried out in Minna and the major signalized roads were the target of the research. The research applied the survey research methodology, which involves carrying volumetric count of vehicles running the red lights on the signalized routes. The research, therefore, found out that, majority of the violators of the traffic signals were the motorcycle riders, closely followed by the tricycle operators; the commercial vehicle owners also form a major percentage of violators of the red light rules in the city. The research, therefore, recommended that strict measures aimed at ensuring immediate compliance with the traffic signals should be implemented, through fines and sanctions on violators to impoundment of offending vehicles. The research concluded that, if instant measures are not put in place to check the menace of the red light running, it will have a serious adverse effect on the social and economic strata of the city.